Privacy Preservation of Genomic and Medical Data - Chamarthy, Sahiti; Moparthi, Nageswara Rao; Rao, Kommaragiri Raghava; Chintala, Venkata Rakesh; Mekala, Janaki Ramaiah; Gade, Charanya; Talluri, Reshitha (Asian Journal of Biological and Life Sciences)
Background: Cancer, characterized by abnormal and uncontrolled cell division, is a major global health concern and a prominent area of research. When a patient is diagnosed with a medical condition, their data is collected for further diagnosis, inference, and research. Given the genetic nature of DNA, the privacy of genomic data is critical, as it affects not only the research subjects but also their families and future generations. Errors in genetic data management can have long-term consequences, making secure data handling essential. Materials and Methods: Various methods have been employed to ensure the privacy and preservation of genomic data, including cloud computing, deep learning, and other advanced tools. These technologies aim to protect patient information while allowing controlled access for medical research, drug discovery, and clinical trials. Strict confidentiality must be maintained between patients and healthcare professionals, with appropriate legal and ethical considerations in place before sharing data. Results: The disclosure of medical and genomic data without consent can lead to harassment, discrimination, and emotional distress for patients. To address these concerns, innovative technologies, algorithms, and software have been developed to securely store and manage patient information. These advancements help mitigate risks associated with data breaches and unauthorized access. Conclusion: Enhancing privacy and security in medical and genomic data is crucial to prevent ethical and societal complications. When data is required for research purposes, obtaining informed patient consent through proper documentation and legal processes is necessary. This review highlights some of the latest algorithms and technologies that ensure the safe preservation of genomic data.
Keywords: Privacy; Cancer; Preservation; Genetic Data.